Key Dimension 2: economic water security - Matheswaran, Karthikeyan; Ludwig, Fulco; Wickramasinghe, Darshana; Sandunika, Nipuni (Asian Development Bank, 2025)
KD2 in AWDO 2025 measures whether countries in Asia and the Pacific have enough reliable water to support sustainable economic growth and reduce water-related economic risks. It assesses four key sectors: the broad economy, agriculture, energy, and industry. Economic water security reflects not only water availability but also how well water is managed, allocated, and governed to support productivity, resilience, and inclusivity.